Long-term memory specificity depends on inhibition of related items. Issue 2 (7th February 2020) - Jeye, Brittany M.; McCarthy, Cassidy R.; Slotnick, Scott D.
ABSTRACT: Long-term memory relies on both accurately retrieving specific details and inhibiting competing information. In the current investigation, we evaluated the specificity of long-term memory representations for faces. During each study phase, participants were presented with neutral Caucasian male and female faces. During the corresponding test phase, old faces, related faces, and new faces were presented and participants made "old"–"new" recognition judgments. Related faces were created by morphing along a continuum in steps of 20% (i.e., 20%, 40%, 60% and 80% morphs) between old faces and new faces (independent ratings indicated that the pairs of to-be-morphed old faces and new faces were perceptually dissimilar). In two experiments, memory representations were very specific as the "old" response rate for old faces was significantly higher than closely related faces (i.e., 20% morphs). Furthermore, there was evidence of memory inhibition, as the "old" response rate for 20% morphs was significantly lower than 40% morphs (the identical pattern of results was observed with a d ' analysis). These findings may reflect an evolutionary advantage for recognising specific faces, which may require inhibition of closely related faces.